Hubungan Tekanan Darah dengan Skor Kualitas Hidup Terkait Kesehatan Pasien Pasca Stroke Iskemik di RSUD Dr. Moewardi - A Annisa Ashliyatul Aziza; O.S Hartanto; Dhoni Akbar Ghozali (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Stroke is a major cause of disability and the fourth leading cause of death. The incidence and prevalence of stroke is directly proportional to the increase in blood pressure, any increase in systolic blood pressure of 10 mmHg and a diastolic blood pressure of 20 mm Hg will increase the incidence of stroke. High blood pressure in people with stroke adversely affect the quality of life of patients. This study was conducted to determine the relationship of blood pressure with quality of life score related to patients health after ischemic stroke in RSUD Dr. Moewardi. Methods: This study was an observational analytic study with cross sectional approach. This study was conducted in August-September 2014 in Neurology Outpatient Clinic of RSUD Dr. Moewardi. Sampling was done by exhaustive sampling, the selection was done by checking the inclusion and exclusion criteria of the sample. Measuring instrument used was a questionnaire Health Related Quality of Life (HR-QOL) SF-36. Data obtained were 36 research subjects and data analysis using multiple linear regression analysis test with SPSS 20.00 for Windows. Results: Seen from the patient's blood pressure, the average systolic blood pressure 143 mmHg and the average diastolic blood pressure of 88 mmHg with an average quality of life of patients with ischemic stroke was 340.27. It was found that there was negative and significant correlation between systolic blood pressure with the quality of life of patients with ischemic stroke b = -3.86; p = 0.003 (p <0.05), there is negative correlation between diastolic blood pressure with the quality of life of patients with ischemic stroke b = -0.77; p = 0771 (p> 0.05), for confounding factors, there were negative and significant correlation between age and quality of life of patients with ischemic stroke b = -4.52; p = 0.008 (p <0.05). Adjusted R2 value = 0.59 showing 59% suitability model in population. Conclusions: Each 1 mmHg increase in systolic blood pressure will lower the quality of life score as much as 3.86 points and each 1 mm Hg increase in age would lower the quality of life score as much as 4.52 points. Keywords: Blood Pressure, Quality of Life, Ischemic Stroke